Comparison of optical coherence tomography angiography to indocyanine green angiography and slit lamp photography for corneal vascularization in an animal model - Mehta, Jodhbir Singh (2018)
Corneal neovascularization (CoNV) could be treated by novel anti-angiogenic therapies, though reliable and objective imaging tools to evaluate corneal vasculature and treatment efficacy is still lacking. Optical coherence tomography angiography (OCTA) –currently designed as a retinal vascular imaging system— has been recently adapted for anterior-segment and showed good potential for successful imaging of CoNV. However, further development requires an animal model where parameters can be studied more carefully with histological comparison. Our study evaluated the OCTA in suture-induced CoNV in a rabbit model compared to indocyanine green angiography (ICGA) and slit-lamp photography (SLP). Overall vessel density measurements from OCTA showed good correlation with ICGA (0.957) and SLP (0.992). Vessels density by OCTA was higher than ICGA and SLP (mean = 20.77 ± 9.8%, 15.71 ± 6.28% and 17.55 ± 8.36%, respectively, P < 0.05). OCTA was able to depict CoNV similarly to SLP and ICGA, though it could better detect small vessels. Moreover, the depth and growth of vessels could be assessed using en-face and serial-scans. This study validated the OCTA in a rabbit model as a useful imaging tool for translational studies on CoNV. This may contribute to further studies on OCTA for anterior-segment including serial evaluation of emerging anti-angiogenic therapies.